Thermophysical Property Measurements of Tetrabutylphosphonium Oxalate (TBPOx) Ionic Semiclathrate Hydrate as a Media for the Thermal Energy Storage System - Miyamoto, Takashi; Koyama, Ryo; Kurokawa, Naruki; Hotta, Atsushi; Alavi, Saman; Ohmura, Ryo (Frontiers in Chemistry, 2020)
With increasing global power demand, thermal energy storage technology could play a role ensuring a sustainable energy supply in power generation from renewable energy sources and power demand concentration. Hydrates have high potential as phase change materials (PCMs) for the use as a thermal energy storage medium. To develop thermal energy storage technology using a hydrate-based material, further investigation of thermophysical properties and the selection of a suitable hydrate are required. Tetrabutylphosphonium oxalate (TBPOx) ionic semiclathrate hydrate contains oxalic acid in salt form, as a guest compound, which is classified as carboxylic acid group with low environmental impact. In the present study, the phase equilibrium temperature and the dissociation heat of TBPOx hydrate were measured. The highest equilibrium temperature of the solid hydrate formed was 9.4 °C at the mass fraction 0.35 of TBPOx in aqueous solution. The largest dissociation heat was 186.0 ± 0.5 kJ·kg-1 at the mass fraction of 0.35. Comparing with other PCMs with close phase equilibrium temperatures, TBPOx hydrate is superior in safety and sustainability. These results indicate that TBPOx hydrate would be suitable as the thermal storage medium for the general air conditioning systems.